2019
DOI: 10.1177/0363546519859542
|View full text |Cite
|
Sign up to set email alerts
|

Concussion in American Versus European Professional Soccer: A Decade-Long Comparative Analysis of Incidence, Return to Play, Performance, and Longevity

Abstract: Background: The incidence and effect of sports-related concussions (SRCs) within the global sport of professional soccer is poorly described. Purpose: To comparatively examine the effects of SRC on athletes in Major League Soccer (MLS) and the English Premier League (EPL) in terms of incidence, return to play (RTP), performance, and career longevity. Study Design: Cohort study; Level of evidence, 3. Methods: Contracts, transactions, injury reports, and performance statistics from 2008 to 2017 were obtained and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…23 However, the proportion of professional English Premier League (EPL), Major League Soccer (MLS), and MLB players participating in respective English and North American sports leagues one-year after sport-related concussion was not significantly different compared with non-concussed players. 7,24 The similarity of the current study's findings with the findings of studies of professional collision sport athletes (NFL & NHL), 21,22 rather than contact sport athletes (EPL, MLS, & MLB), 7,24 one-year following sport-related concussion may be explained by the proportion of collision sport athletes in our study sample and the rate of athlete attrition in collision sports that is due to injury.…”
Section: Discussionsupporting
confidence: 81%
“…23 However, the proportion of professional English Premier League (EPL), Major League Soccer (MLS), and MLB players participating in respective English and North American sports leagues one-year after sport-related concussion was not significantly different compared with non-concussed players. 7,24 The similarity of the current study's findings with the findings of studies of professional collision sport athletes (NFL & NHL), 21,22 rather than contact sport athletes (EPL, MLS, & MLB), 7,24 one-year following sport-related concussion may be explained by the proportion of collision sport athletes in our study sample and the rate of athlete attrition in collision sports that is due to injury.…”
Section: Discussionsupporting
confidence: 81%
“…A possible explanation for this may be the management of RTP following concussion. In elite soccer, Ramkumar et al 7 demonstrated that players returning through more aggressive protocols suffered a decrement in performance versus those managed more conservatively.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also the potential for impaired playing performance, increased musculoskeletal injury risk and, in elite sport, limitation of career length and earning potential in the short-and medium-term following concussion. [3][4][5][6][7] There are also concerns around repetitive 'sub-concussive' impacts and the potential for these accumulated impacts to be as important in the short-and long-term brain health of athletes. [8][9][10] Improved understanding of head impact injuries in cricket is important, particularly given approximately 70% of concussions occurring after such injuries are not diagnosed at the time of the strike.…”
Section: Introductionmentioning
confidence: 99%
“…In the Contact category, sports with less frequent and often not purposeful shock on the head (e.g., basketball, soccer, and gymnastics) were included ( Table 1 ; Reynolds et al, 2017 ). The remaining sports were classified under the No-Contact category (e.g., athletics, archery, and swimming) ( Ramkumar et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%